Penggunaan Model Make a Match untuk Meningkatkan Kemampuan Mufradat Siswa Madrasah Ibtidaiyah - Edidarmo, Toto; Dardiri, Ahmad; Khairi, Andhika (Kalimatuna: Journal of Arabic Research, 2022)
Researchers found obstacles in the vocabulary teaching process, including not using effective learning strategies and models in learning Arabic vocabulary. This study aims to reveal vocabulary learning procedures and the effectiveness of the make-a-match model in vocabulary teaching. This research used a quantitative approach and quasi-experimental methods with a non-equivalent group design model. The sample from this study was comprised of 22 students in grade 5A, Nurul Huda Sampora, as an experimental group, and 22 students in grade 5B, as a control group. The data collection techniques used are direct observation, personal interviews, pre-test and post-test, as well as documentation. Researchers used the T test formula in analyzing the data. Researchers concluded that the make a match model in the teaching of Arabic vocabulary is effective.